Validation of the Simplified Chinese Version of the Body Image Disturbance Questionnaire-Scoliosis. Issue 21 (November 2015) - Bao, Hongda; Yan, Peng; Lonner, Baron; Qiu, Yong; Ren, Yuan; Zhu, Zezhang; Liu, Zhen; Zhu, Feng
Abstract : Study Design: Cross-cultural adaptation and validation of the Body Image Disturbance Questionnaire-Scoliosis (BIDQ-S). Objective: The aim of this study was to validate the Chinese version of BIDQ-S (C-BIDQ-S) in adolescent idiopathic scoliosis (AIS) patients in Mainland China. Summary of Background Data: A modified version of the Body Image Disturbance Questionnaire instrument has been validated in AIS patients (BIDQ-S) to assess the perception of spinal appearance and psychological disturbance. However, there is no culturally adapted, reliable, and validated BIDQ-S for the Chinese population. Method: The BIDQ-S was translated into simplified Chinese, and the cross-cultural adaptation of the original BIDQ-S was performed according to international guidelines. A total of 100 AIS patients were recruited into this study. Validation including reliability, internal consistency, and convergent validity was evaluated by comparing the C-BIDQ-S with Scoliosis Research Society (SRS)-22 and Spinal Appearance Questionnaire (SAQ) instruments. The relationship between C-BIDQ-S score and patient characteristics was also assessed. Results: Internal consistency for the C-BIDQ-S was satisfactory with a Cronbach alpha value of 0.877. The construct validity test demonstrated significant correlations between the C-BIDQ-S score and all SRS-22 domains as well as between the C-BIDQ-S score and most of SAQ domains. Although the C-BIDQ-S score was not correlated with age or BMI, patients with Cobb angle >40° presented a significantly higher (poorer) C-BIDQ-S score. Conclusion: The Simplified Chinese version of BIDQ-S showed good internal consistency, strong psychometric properties, and satisfactory reliability. This concise questionnaire is suitable for widespread use in Mainland China.